The Role Of Innovation Capability In Mediating The Effect Of Strategic Agility On Business Performance Of Smes In The Food And Beverage Sector In Cimahi - Azzam Tiar Busyeri; Rofi Rofaida; Hady Siti Hadijah; Asep Kurniawan (Dinasti International Journal of Education Management And Social Science, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Cimahi City possess strategic potential, particularly in the food and beverage sector. Cimahi is one of the cities experiencing growth in the number of MSMEs, with a growth rate of 50.24%. However, the increase in the number of MSMEs has not been accompanied by consistent revenue growth, which has fluctuated from 2019 to 2023. Several challenges have been identified, including a lack of basic entrepreneurial knowledge among the workforce, insufficient self-reliance in entrepreneurship, and limited proficiency in the use of technology. To address these performance issues, it is crucial for MSME actors to create added value by strengthening strategic agility and innovation capability. The objective of this study is to examine the impact of strategic agility on business performance, mediated by innovation capability. The study sample consists of 106 MSMEs, selected using probability sampling with a cluster sampling technique. Descriptive analysis results categorize business performance and innovation capability as moderate, while strategic agility is categorized as high. The research findings indicate that strategic agility does not affect innovation capability, strategic agility influences business performance, innovation capability affects business performance, and innovation capability does not mediate the influence of intellectual capital on business performance.